2016
DOI: 10.1002/app.43570
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted synthesis of chitosan biguanidine hydrochloride and its antioxidant activity in vitro

Abstract: Chitosan biguanidine hydrochloride (CSGH) was synthesized by guanidinylation of chitosan hydrochloride (CSH) under microwave irradiation and characterized by Fourier transform infrared spectroscopy, gel permeation chromatography, and element analysis. The antioxidant activity of CSGH was evaluated by both chemical and cellular methods. The results showed that CSGH was better than CSH but slightly inferior to ascorbic acid (Vc) for scavenging 2,2‐diphenyl‐1‐picryl‐hydrazyl (DPPH) free radicals, and the DPPH• sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…All these results conrmed that COSG was synthesized successfully. 52,53,59 The 13 C-NMR spectra of the COS and COSG are shown in Fig. 5.…”
Section: Cosg Characterizationmentioning
confidence: 99%
“…All these results conrmed that COSG was synthesized successfully. 52,53,59 The 13 C-NMR spectra of the COS and COSG are shown in Fig. 5.…”
Section: Cosg Characterizationmentioning
confidence: 99%
“…Sang et al 46 synthesized quaternized carboxymethyl chitosan containing guanidine groups, which demonstrated strong antimicrobial activity. Our previous studies found that biguanidine hydrochloride displayed excellent antioxidant ability, 47 and chitooligosaccharide guanidine was likely to promote transmembrane of GLUT4 by improving the phosphorylation level of Akt, thereby increasing glucose uptake of skeletal cells. 48 However, up to now, there are few reports about the effect of chitosan guanidine derivatives on insulin resistance hepatic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting those groups onto chitosan normally requires a reaction conducted at an elevated temperature. One of the recently developed approaches for heating the reaction system is microwave assisted heating which appears to be more homogeneous, selective and efficient in comparison with the conventional heating method [ 16 , 17 , 18 ]. The microwave irradiation heating process also resulted in fast reaction with few or no side products.…”
Section: Introductionmentioning
confidence: 99%